ICOS Co-Stimulation: Friend or Foe? - Wikenheiser, Daniel J.; Stumhofer, Jason S. (Frontiers in Immunology, 2016)
Over the last 15 years, the inducible T cell co-stimulator (ICOS) has been implicated in a wide variety of immune outcomes, including the induction and regulation of Th1, Th2, and Th17 immunity. In addition to its role in directing effector T cell differentiation, ICOS has also been consistently linked with the induction of thymus-dependent Ab responses and the germinal center reaction. ICOS co-stimulation, therefore, appears to play a complex role in dictating the course of adaptive immunity. In this article, we summarize the initial characterization of ICOS and its relationship with the related co-stimulatory molecule CD28. We then address the contribution of ICOS in directing an effector T cell response, and ultimately disease outcome, against various bacterial, viral, and parasitic infections. Next, we assess ICOS in the context of TD Ab responses, connecting ICOS signaling to Tfh cell differentiation and its role in the germinal center reaction. Finally, we address the link between ICOS and human autoimmune disorders, and evaluate potential therapies aiming to mitigate disease progression by modulating ICOS signaling.